Pengaruh Harga Jual Dan Brand Image Terhadap Minat Beli Produk Ekspor Luxcrime Di Platform Tiktok Shop - Andi Nabila Maharani; Rudianto Hermawan (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This research aime d to analyze the effect of selling price and brand image on the purchasing interest of Luxcrime brand cosmetic export products on the TikTok Shop platform. The phenomenon of increasing use of TikTok as a social media and e-commerce platform is an important background for companies to maximize their digital marketing strategies. The research method used was descriptive quantitative with data collection techniques through the distribution of questionnaires to 100 respondents who were TikTok Shop users and familiar with Luxcrime products. The independent variables in this research included selling price (X1) and brand image (X2), while the dependent variable was consumer purchasing interest (Y). The data was analyzed using multiple linear regression to test the hypothesis and determine the significance of the relationship between variables. The results of the analysis showed that both selling price and brand image had a positive and significant influence on consumer purchasing interest, both partially and simultaneously. This finding had strategic implications for businesses, particularly in the beauty industry, to maximize brand image and competitive pricing as an effective approach in increasing consumer appeal and purchase volume in the era of digital marketing. Keywords: Selling Price, Brand Image, Purchase Interest, TikTok Shop, Luxcrime Cosmetics